On the Concept of Organizational Goal - Simon, Herbert A. (Administrative Science Quarterly, 1964)
It is difficult to introduce the concept of without reifying the organization-treating it as something more than a system of interacting individuals. On the other hand, the concept of appears indispensable to organization theory. This paper proposes a definition of organizational goal that resolves this dilemma. The of an action is seldom unitary, but generally consists of a whole set of constraints the action must satisfy. It appears convenient to use the term organizational goal to refer to constraints, or sets of constraints, imposed by the role, that have only an indirect relation with the personal motives of the individual who fills the role. More narrowly, organizational goal may be used to refer particularly to the constraint sets that define roles at the upper levels of the administrative hierarchy. In actual organizations, the decision-making mechanism is a loosely coupled, partially decentralized structure in which different sets of constraints may impinge on decisions at different locations. Although the description of goals is consequently complex, the concept of can still be introduced in an entirely operational manner.' Herbert A. Simon is professor of administration and psychology in the Graduate School of Industrial Administration, Carnegie Institute of Technology.